Nilai Moral Dalam Cerpen عدو المعيز Karya Kamil Kailani (Kajian Sosiologi Sastra) - Arifah Amelia Istiqomah; Azkiya Fioda Reinawati; Khasanah Arie Puji Astuti; Tri Rahayu; Uswatun Uswatun (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
This study aims to provide an explanation and description of some of the moral values ​​contained in the short story عدو المعيز by Kamil Kailani. So that in this study using descriptive qualitative research methods and using a sociological approach to literature. The short story عدو المعيز by Kamil Kailani was used as the object of research. This research data uses several text sentences contained in the story by reading and analyzing then recording something that shows the moral value in the short story text. In addition, it also uses secondary data that supports this research. Then, the results of the analysis of the short story عدو المعيز there are moral values ​​which include: human relations with oneself, human relations with humans, and human relationships with God. Because it is very important to add experience and insight, as well as in terms of behavior in everyday life. Because today there are still many behaviors that deviate from morals in society. And it would be nice if we minimize it with ourselves first. Keywords: Moral Values; Short Stories; عدو المعيز; Sociology Of Literature.